Studies on Improve Survivability and Shelf Life of Carrier Using Liquid Inoculation of Pseudomonas striata - Elango, R (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Biofertilizers are also known as microbial inoculants or bioinoculants. It is a product of selected, beneficial and live microorganisms which helps to improve plant growth and productivity, mainly through supply of plant nutrients. Death of the organisms in the inoculated seed is one of the important factors contributing the failure of inoculation response in field condition. This present study was conducted to improve the shelf life and survivability of inoculant in liquid form. Pseudomonas straita was used as an inoculant which having phosphate solubilizing capacity Three different treatment like vermiculite, lignite and liquid inoculants were used for survival of Pseudomonas straita. . Four different broths were used such as GPS (Glucose peptone broth), PVB (Pikovasky broth), NB (Nutrient broth) and PSB (Peptone sodiumchloride broth) to prepare liquid bioinoculants. Upon that liquid inoculant shows high phosphate solubilizing efficiency than other two treatments and also luquid inoculant show more survivability of Pseudomonas straita than other two treatments. Based on the results, liquid inoculant is considered as best bioinoculants in growth of paddy than control and other two treatments.